Estudo da influência da adição de compostos de boro na resistência à oxidação de refratários a base de carbeto de silício-liga de nitreto. - Rodrigues, Cesar Augusto Frasson (Universidade Federal de São Carlos, 2004)
In this work, boron was added in a commercial silicon carbide bonded silicon nitride refractory and its influence has been evaluated. These materials have been used as high temperature structural ceramic due to their properties combination, as the hot modulus of rupture, abrasion resistance, excellent thermal conductivity, good thermal shock resistance and good corrosion resistance. To prepare the studied compositions, boron compounds were added during mixing stage and sintered at 1450o C in a nitrogen atmosphere. Some compositions were tested on a first stage using hot modulus of rupture tests and X ray diffractions. On a second stage, modulus of rupture at room temperature, scanning electronic microscopy and mainly oxidation tests (980 and 1230o C / 200 hours) were performed and valued. The obtained results were compared with the commercial refractory. As the weight gain is an oxidation indicative, samples made with boron nitride have indicated trends to be a good alternative to increase the oxidation resistance. Besides, boron additives contributed to crystallize the silica film in the samples and contributed to getting a better oxidation resistance. The oxygen diffusivity is bigger in the vitreous silica than in the crystalline, and due to this crystallization, boron additives have shown a good opportunity to decrease the oxidation rate. The results obtained by SEM showed silicon nitride fibers, mainly inside the porous. Moreover, as informed on the paper references, boron has contributed to form air bubbles in the silica film, but without bubbles rupture. These ruptures could be responsible to increase the oxidation rate in the silicon carbide surfaces. Also, spherulits were not observed in the oxidized film.
Influence of boron compounds addition in the silicon carbide - nitride bonded refractoryes oxidation resistence
Keywords: Material cerâmico; Materiais refratários; Carbeto de silício; Oxidação; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA